Continuous-Flow Synthesis of the Nucleobase Unit of Remdesivir. (February 2023) - Guo, Yongxing; Liu, Minjie; Jiang, Meifen; Tao, Yuan; Cheng, Dang; Chen, Fen-Er
Abstract: In this work, the nucleobase unit of the antiviral drug remdesivir, 7-bromopyrrolo[2, 1- f ][1, 2, 4]triazin-4-amine, was synthesized through five-step continuous flow. By adapting batch synthetic chemistry, 7-bromopyrrolo[2, 1- f ][1, 2, 4]triazin-4-amine was successfully produced through sequential flow operations from the widely available and inexpensive starting material pyrrole. Under optimal flow conditions, 7-bromopyrrolo[2, 1- f ][1, 2, 4]triazin-4-amine was obtained in 14.1% isolated yield in a total residence time of 79 min with a throughput of 2.96 g·h −1 . The total residence time was significantly shorter than the total time consumed in batch procedures (> 26.5 h). In flow, the highly exothermic Vilsmeier–Haack and N-amination reactions involving hazardous and unstable intermediates, oxidative liquid–liquid biphasic transformation, and a bromination reaction requiring strict cryogenic conditions are favorably facilitated. The salient feature of this synthesis is that the workup procedures are fully integrated into the reaction sequences by deploying dedicated equipment and separation units, thus forming a streamlined continuous-flow system that maximizes the overall process efficiency. This method represents a greener and more sustainable process to prepare this nucleobase unit with high efficiency and safety.